UJI TOKSISITAS EKSTRAK ETANOL DAUN JAMBU BIJI AUSTRALIA (Psidium guajava L) DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Nofita Nofita; Ade Maria Ulfa; Miera Delima (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
ABSTRACTGuava is one of the plants that can traditionally be used for the treatment of diseases. Many kinds of guava, one of which is the Australian guava has the characteristics of roots, stems, leaves, dark red fruit. This study aims to determine the toxicity of the ethanol extract of Australian guava leaves (Psidium guajava L) using the BSLT (Brine Shrimp Lethality Test) method and determine the chemical content of Australian guava leaves (Psidium guajava L). The extract was made by the ultrasonic method using 96% ethanol solvent. Toxicity tests were carried out using 48-hour-old Artemia salina Leach shrimp larvae. The toxic effect of the extract was identified by the percentage of shrimp larvae mortality using probit analysis (LC50). From the research results, phytochemical content includes tannins, flavonoids, alkaloids, terpenoids and saponins, and flavonoid compounds have the highest content compared to the others. Research shows that the ethanol extract of Australian guava leaves is of a moderate category (LC50 441,977 ppm).Keywords :Australia guava leaves, BSLT, Artemia salina L, Ultrasonic